2015
DOI: 10.1080/23273798.2015.1072638
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic priors shape categorical perception

Abstract: This article reviews recent literature on the role of top-down feedback processes in semantic representations in the brain. Empirical studies on perception and theoretical models of semantic cognition show that sensory input is filtered and interpreted based on predictions from higher order cognitive areas. Here, we review the present evidence to the proposal that linguistic constructs, in particular, words, could serve as effective priors, facilitating perception and integration of sensory information. We add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Furthermore, recent studies have revealed that neural networks of color perception show strong connections between basic visual areas V1 and V4 and inferotemporal and nearby regions associated with categorization (Walsh, 1999;Roe et al, 2012;Gilbert and Li, 2013;Simanova et al, 2015;Winawer and Witthoft, 2015). Moreover, an fMRI study showed activation of language regions during color perception, supporting the notion of an interaction between higher level cognition and perceptual processes (Siok et al, 2009;Brouwer and Heeger, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, recent studies have revealed that neural networks of color perception show strong connections between basic visual areas V1 and V4 and inferotemporal and nearby regions associated with categorization (Walsh, 1999;Roe et al, 2012;Gilbert and Li, 2013;Simanova et al, 2015;Winawer and Witthoft, 2015). Moreover, an fMRI study showed activation of language regions during color perception, supporting the notion of an interaction between higher level cognition and perceptual processes (Siok et al, 2009;Brouwer and Heeger, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…It is generally assumed that overlap in the computational mechanisms that underlie conceptual and sensory-motor processing reflect bottom-up sensory-motor effects on higher-order cognition. However, factors like language-mediated categories can constrain sensory perception (Brouwer & Heeger, 2013; Puri, Wojciulik, & Ranganath, 2009; Lee & Noppeney, 2014), suggesting that shared computational processes might partially reflect top-down effects of linguistic priors on perception (Simanova, Francken, de Lange & Bekkering, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that a larger reward for one of the response options or increased likelihood of occurrence of two events results in an enhanced starting point of evidence accumulation for that particular response (Mulder et al, 2012). It has recently been proposed that language affects perception by setting predictive priors that sharpen perceptual representations (Simanova et al, 2016). Kinoshita et al (2017) indeed showed that the brief presentation of a color word followed by the presentation of a color sign to be categorized resulted in a facilitation effect that translated to boundary separation and starting-point modulations.…”
Section: Congruency With the Target Words Facilitates Information Promentioning
confidence: 99%
“…By "schemata" we mean a set of features/beliefs that subjectively reflect the social category of gender and subsequently influence our decisions. Put differently, language can introduce a top-down bias that can influence both visual perception (Simanova et al, 2016) and social decision making (Kunda and Sherman-Williams, 1993).…”
Section: Effects Of Words On Processing Speed Of Gendered Facesmentioning
confidence: 99%